Clustering Strategy in Intellectually Gifted Children: Assessment Using a Collaborative Recall Task. (April 2017) - Zhang, Huan; Zhang, Xingli; He, Yunfeng; Shi, Jiannong
This study examined three aspects of the clustering strategy used by participants: the differences of clustering strategy between intellectually gifted and average children; the relationship between clustering strategy and recall performance in intellectually gifted and average children; and the differences in recall performance on collaborative recall task of intellectually gifted and average children. Thirty-eight intellectually gifted and 44 intellectually average children were recruited, and their collaborative and individual recall performances were tested. The results showed that intellectually gifted children had better clustering strategy than their peers when adjusted ratio of clustering scores were calculated ( p < .01); clustering strategy positively correlated with recall performance in intellectually average children ( p < .05), while no such correlation was found in intellectually gifted children ( p = .95); there was no collaborative inhibition in the gifted group ( p = .82). These findings partly resolve the conflicts in individual research and expand on the conclusions regarding collaborative memory.